The frequency of asthma exacerbations and healthcare utilization in patients with asthma from the UK and USA - Suruki, Robert Y. (BMC Pulm Med, 2017)
BACKGROUND: Asthma exacerbations are frequent in patients with severe disease. This report describes results from two retrospective cohort studies describing exacerbation frequency and risk, emergency department (ED)/hospital re-admissions, and asthma-related costs by asthma severity in the US and UK. METHODS: Patients with asthma in the US-based Clinformatics™ DataMart Multiplan IMPACT (2010–2011; WEUSKOP7048) and the UK-based Clinical Practice Research Datalink (2009–2011; WEUSKOP7092) databases were categorized by disease severity (Global Initiative for Asthma [GINA]; Step and exacerbation history) during the 12 months pre-asthma medical code (index date). Outcomes included: frequency of exacerbations (asthma-related ED visit, hospitalization, or oral corticosteroid use with an asthma medical code recorded within ±2 weeks) 12 months post-index, asthma-related ED visits/hospitalization, and asthma-related costs 30 days post-index. Risk of a subsequent exacerbation was determined by proportional hazard model. RESULTS: Of the 222,817 and 211,807 patients with asthma included from the US and UK databases, respectively, 12.5 and 8.4% experienced ≥1 exacerbation during the follow-up period. Exacerbation frequency increased with disease severity. Among the 5,167 and 2,904 patients with an asthma-related ED visit/hospitalization in the US and UK databases, respectively, 9.2 and 4.7% had asthma-related re-admissions within 30 days. Asthma-related re-admission rates and costs increased with disease severity, approximately doubling between GINA Step 1 and 5 and in patients with ≥2 versus <2 exacerbations in the previous year. Risk of a subsequent exacerbation increased 32–35% for an exacerbation requiring ED visit/hospitalization versus oral corticosteroids. CONCLUSION: Increased disease severity was associated with higher exacerbation frequency, ED/hospitalization re-admission, costs and risk of subsequent exacerbation, indicating that these patients require high-intensity post-exacerbation management. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12890-017-0409-3) contains supplementary material, which is available to authorized users.